Development of Student Worksheet Oriented on PBL and Science Literacy to Improve Students' Critical Thinking Skills on Buffer Solution Material - Fadhilatur Rochmatin; Muchlis (PendIPA Journal of Science Education, 2023)
This research intends to create a student worksheet that can be used to help students enchance their critical thinking skills. Validity, practicality, and effectiveness are taken into consideration when evaluating the viability of a student worksheet. The validity of the student worksheet is evaluated by specialists. Practice was based on student responses supported by activities during learning. Meanwhile, effectiveness was based on improving students' critical thinking skills in terms of classical learning completeness, N-gain, and non-parametric statistical tests. This research employed the Research and Development method devised by Borg and Gall, with 18 students from grade XI SMAN 20 Surabaya serving as research subjects. The research instruments used were validation sheets, response questionnaires, student activity observation sheets, and pretest and posttest question sheets. The results indicated that the student worksheet was usable. The evaluation results show the validity of the student worksheet, which received a score mode of 5 with a very good category. The practicality of student worksheet is seen from the positive response of students with a range of 88.9%-100% which is categorized as very practical. It is also supported by activities that are more relevant than irrelevant activities. The effectiveness of student worksheet is shown by the 89% completion of classical learning, medium and high N-gain criteria with successive percentages of 38.89% and 61.11%, and hypothesis tests with Sig. < 0.05 values.